2022
DOI: 10.52547/ijmpp.7.3.772
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Pain Catastrophizing based on Pain Anxiety Symptoms and Cognitive Flexibility in Cancer Patients

Abstract: The purpose of this study was to investigate the prediction of pain catastrophizing based on pain anxiety symptoms and cognitive flexibility in cancer patients Method and Materials: In this cross-sectional study all cancer patients in Tehran in 2021-22 were the target population. Among this population 250 cancer patients were selected via candidate and at reach sampling method. Then the selected patients completed the Paknejad et al.`s Pain Anxiety Symptoms (2014), Sullivan et al. `s Pain Catastrophizing Pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…64 Also, the role of mood and mental pain confirms the findings of this research. Our study showed a relationship between mental pain and pain perception, as we can refer to a study by e Raiisi et al (2022). According to the results, mental pain plays a mediator role between pain anxiety and perception.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…64 Also, the role of mood and mental pain confirms the findings of this research. Our study showed a relationship between mental pain and pain perception, as we can refer to a study by e Raiisi et al (2022). According to the results, mental pain plays a mediator role between pain anxiety and perception.…”
Section: Discussionsupporting
confidence: 64%
“…According to the results, mental pain plays a mediator role between pain anxiety and perception. 36 Other studies have revealed that people who suffer from depression have more complaints about pain. Regarding the vital role of emotion and mood in the perception of dental pain, the significant role of psychological factors should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation